Estimated 24-hour urinary sodium excretion and sodium-to-potassium ratio among Japanese elementary school teachers and school lunch cooks - Chikako Seko; Mikoto Yamashiro; Kiyoko Odani; Sayori Wada; Kengo Yoshii; Akane Higashi (Clinical and Experimental Hypertension, 2021)
Background:Dietary salt intake is largely responsible for increase in blood pressure that is commonly seen with aging. In our previous study carried out in 2015, we calculated the 24-hour urinary sodium excretion and sodium-to-potassium (Na/K) ratio among elementary school children. In the present study, we aimed to examine the same items among the school children’s teachers and lunch cooks.Methods:Of 153 recruited participants, urine samples were collected from 129 subjects (84.3%), and 124 subjects (81.0%; 37 male teachers, 65 female teachers, and 22 female cooks) whose dietary habits were confirmed were included in the final study analysis.Results: The median estimated 24-hour urinary salt excretion (g/day) was 8.2 in male teachers, 7.4 in female teachers, and 8.9 in cooks. The median urinary Na/K ratio (mEq/mEq) was 4.1 in male teachers, 3.6 in female teachers, and 4.0 in cooks. In both male and female teachers and cooks, no association was found between urinary salt excretion or urinary Na/K ratio and an awareness of the need to restrict salt intake. The proportion of subjects with both a urinary salt excretion and Na/K ratio above the median was high in male teachers and cooks, whereas the proportion of subjects who scored below the median in both tests was high in female teachers.Conclusion:It should be considered that elementary school teachers and cooks who have been provided with the results of their own salt excretion could realize the importance of reducing salt consumption from early childhood and the continuous salt intake reduction education for children.